The Evolution of Fetal Surgery - Knezevich Michelle; M. Koehler Shannon; Wagner Amy (Journal of Fetal Surgery, 2017)
Fetal surgery is the newest surgical specialty with a compelling history. The development of fetal surgery began in primates and lambs and, in its most basic form, was first performed in humans in 1965. Since its introduction, the field has expanded and changed dramatically. Several of these changes have involved the ethical aspect of fetal surgery. This field conflicts with the Hippocratic oath mantra of “first do no harm” as one of the patients, the mother, receives no benefit from these procedures. The ethical dilemma resulted in stringent inclusion and exclusion criteria for fetal operations. Initially, fetal surgery was only indicated for life-threatening conditions of the fetus but is now offered in some disease processes to improve quality of life for the child. As the field has matured, it has grown to encompass numerous different types of fetal interventions. Similar to other areas of surgery, the trend has been to migrate from more invasive to less invasive procedures. Currently, some of these therapies are performed entirely percutaneously. Theoretically, this trend would improve outcomes for both the mother and fetus. While this has generally proven true, there are some important exceptions to this rule. Finally, as the field continues to evolve, much research is being performed looking at possible new types of fetal interventions. Some of these procedures, such as fetal stem cell therapy and fetal gene therapy, could change the face of modern medicine.
Keywords: Congenital Pulmonary airway malformation (CPAM)